Unusual Orbital Tumor Diagnosis and Management of Ocular Follicular Lymphoma: A Case Report - Pastrana, Victor; Rodriguez-Marrero, Yilena; Sanchez, Daniel; Morales, Dagoberto J.; Sanchez, Roberto; Morse, William; Barreneche, Gal; Wiss, Caroline (Archives of Clinical and Medical Case Reports, 2024)
Orbital follicular lymphoma is a subtype of orbital lymphoma, which is a group of lymphoproliferative disorders affecting the orbit. Early diagnosis and intervention are crucial for preserving vision and preventing systemic spread. A 69-year-old Hispanic female presented with a one month history of double vision. MRI revealed a 3.7 cm enhancing mass in the right superior oblique muscle. Biopsy confirmed low-grade follicular lymphoma. PET-CT showed localized and mild systemic involvement. Bone marrow biopsy indicated no lymphoma involvement. The patient is undergoing targeted therapy with bendamustine and rituximab every 28 days for 4 cycles, with regular follow-ups. This case underscores the importance of considering lymphoma in patients with unusual ocular symptoms and highlights the role of comprehensive imaging, biopsy, and bone marrow examination in diagnosis and treatment planning.